(untitled) (Research, Society and Development, 2020)
The objective of the study was to evaluate the degree of clogging and the relative flow over time and at different operating pressures of a surface drip system. The experiment was carried out in a greenhouse installed in the experimental area of FGoiano - Campus Rio Verde. The experimental design used was in randomized blocks, analyzed in a 4 × 6 factorial scheme, with three replications. The treatments consisted of four pressures (0.8, 1.1, 1.4 and 1.7 kgf) and six operating times (600, 650, 700, 750, 800, 850 hours). The irrigation system used was the surface drip equipped with self-compensating emitters model iDrop PC-PCDS with flow rate of 2.2 L h -1 and operating pressure of 5 to 45 mca, inserted in a low density polyethylene hose of 16 mm, with 0.5 m spacing. After the flow data was tabulated, the calculations of the absolute uniformity coefficient, degree of clogging, relative flow and statistical uniformity coefficient were performed. For the operating pressure of 0.8 and 1.4 Kfg, the operating time of 744 and 555 hours, respectively, promoted the lowest GE value (<3.7%). The increasing pressure variations raised the AUC until reaching its maximum value of approximately 96.20% under the operating pressure of 1.24 kgf. The highest relative flow and Statistical uniformity coefficient are verified in the initial operating time (600 hours).